A review of phenomenological spray penetration modeling for diesel engines with advanced injection strategy. (August 2020) - Liu, Long; Peng, Yan; Liu, Dai; Han, Changfu; Zhao, Ningbo; Ma, Xiuzhen
Driven by the increasingly remarkable problems of environmental pollution and energy crisis, the combustion optimization of diesel engine seems to be more urgent than ever, therefore, advanced injection strategies are gradually proposed and employed in modern diesel engines. Phenomenological model, which serves as an effective tool to conduct the parametric study on the spray penetration, needs to be improved to fit the intensified injection condition. Since that there are no attempts to review the spray penetration model developments, in order to help to build a comprehensive understanding of diesel spray propagation, this article briefly summarized the early history and introduced the widely used classical and improved phenomenological spray penetration models. Besides, to provide a helpful reference for selection of suitable models, the modeling methods were analyzed and features and simulation of various models were discussed and compared. After that, the trend of modeling methods and promising directions for future spray modeling were suggested.